“Insights into Behavioral Challenges in ASD Children in Peshawar Autism Centers and Parental Perspectives on its Management: A mixed method study” - Malak Amanullah Khan; Hafsa Habib; Mifrah Rauf sethi; Shayan Sharif; M Afaq Khan Yousafzai (Research Journal of Psychology, 2024)
Autism spectrum disorder (ASD) is a complex brain development condition that includes repetitive behaviors, limited interests, and challenges with social skills and communication. To understand common behavioral issues in children with autism and to learn how parents view the available treatments and their effectiveness. A mixed method study was conducted on Autistic children in Peshawar Autisms center in which a CBCL questionnaire were filled by parents of total sample 250(Open epi with 95%confidence interval) in first phase within 3 months (Nov/2023-jan/2024) while 20 in-depth interviews of 09 questions were taken from their parents in 2nd phase within 15 days (Feb /2024). Random sampling was used for quantitative data while purposive sampling was used for quantitative data collection. The qualitative data was analyzed using Virginia Braun and Victoria Clarke’s thematic analysis method through NVivo 14, while the quantitative data was analyzed using SPSS 26 for measuring frequency, mean and total score. In all, 250 questionnaires were filled by parents of Autistic children with mean age of 3.5years. Among them the most prevalent behavioral issues were aggression (24%), attention problems (19%), withdrawal (16%), and somatic problems (15%). 44 codes were generated from the qualitative interviews, which further divided into 15 categories and emerged into 4 themes. (1) Parental Challenges in Rearing ASD Children, (2) Goals and Effectiveness of early intervention in ASD, (3) Key Components of Successful Autism Management, (4) Parental Satisfaction & Suggestions. Majority of parents (70%) expressed full satisfaction with the available resources for managing autism, and they have observed improvements in their children's behavior like Attention & verbal communication through various early interventions. In Peshawar, early intervention at autism centers helps manage common behavioral issues aggression and attention issues in autistic children. Parents advise seeking timely support and awareness for better outcomes. Keywords: Autism Spectrum Disorder; Child; Parent; Therapies.